ICTV Virus Taxonomy Profile: Caliciviridae. (1st October 2019) - Vinjé, Jan; Estes, Mary K.; Esteves, Pedro; Green, Kim Y.; Katayama, Kazuhiko; Knowles, Nick J.; L'Homme, Yvan; Martella, Vito; Vennema, Harry; White, Peter A.; ,
Abstract : The family Caliciviridae includes viruses with single-stranded, positive-sense RNA genomes of 7.4–8.3 kb. The most clinically important representatives are human noroviruses, which are a leading cause of acute gastroenteritis in humans. Virions are non-enveloped with icosahedral symmetry. Members of seven genera infect mammals ( Lagovirus, Norovirus, Nebovirus, Recovirus, Sapovirus, Valovirus and Vesivirus ), members of two genera infect birds ( Bavovirus and Nacovirus ), and members of two genera infect fish ( Minovirus and Salovirus ). This is a summary of the International Committee on Taxonomy of Viruses (ICTV) Report on the family Caliciviridae, which is available at ictv.global/report/caliciviridae .